Nanostructured proton-exchange membranes from self-cross-linking perfluoroalkyl-free block-co-polymers - Auffarth, Sebastian; Maier, Maximilian; Martschin, Philipp; Stigler, Theresa; Wagner, Maximilian; Böhm, Thomas; Hutzler, Andreas; Thiele, Simon; Kerres, Jochen (Materials Today Advances, 2024)
A sustainable hydrogen economy relies on fuel cells and electrolyzers, which heavily depend on ion-conducting perfluoroalkylated materials such as Nafion or Aquivion. Together with other perfluorinated alkyl substances, their environmental accumulation, and the rising awareness of risks to human health stress the need for alternative materials. Based on block-co-polymers from octylstyrene and pentafluorostyrene, we present nanostructured proton-exchange membranes. In contrast to problematic perfluorinated alkyl constituents, the involved aromatic fluorine atoms allow mild functionalizations to form tetrafluorostyrene sulfonic acid. Meanwhile, the nonpolar block reduces the stiffness of the material. By introducing a new preparation technique, controlled mitigation of the thiol cross-linking allows membrane self-reinforcement during drying. The reinforcing cross-links enhance the dissolution stability and reduce the water uptake after 24 h down to 33 wt% at 85 °C. Cross-section imaging visualizes the influence of varying di- and tetrablock-co-polymer backbones on the membrane nanostructure with sizes between 20 and 35 nm. The membranes feature proton conductivities comparable to commercial materials at low humidity levels, surpassing commercial Nafion XL at 87 % relative humidity with up to 79 mS cm−1 at 105 °C. As first successful H2/air fuel cell tests achieve maximum power densities of up to 0.7 W cm−2, the nanostructured polymer membranes are a promising candidate for future fuel cell and electrolyzer applications without problematic perfluorinated alkyl substances.
CRIS-Team Scopus Importer:2024-08-16
Keywords: Nanophase separation; PFAS-free; Proton-exchange membrane; Self-assembly; Tetrafluorostyrene sulfonic acid; Thiol cross-linking